Analysis of Speech Act Theory in the News â€œIndonesia's Urge on Access to Education for Women in the Talibanâ€ on the Tempo.co page - Rizka Akmalia; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to examine pragmatics in speech act theory in the news "Indonesia's insistence on access to education for women in the Taliban" on the Tempo.co page, while the speech act theory was first initiated by J.L Austin which was later developed by J.R Searle. In this study using a descriptive qualitative method with a mechanism for collecting literary sources, in-depth reading of literary sources, recording important information, analysis, and conclusions. This study analyzes the theory of speech acts in the form of locutionary, illocutionary and perlocutionary in the news on the Tempo.co page. The results of this study indicate: (1) Tempo.co contains the theory of locutionary, illocutionary and perlocutionary speech acts, (2) 2 assertive illocutionary speech acts, 2 directive illocutionary acts, 2 expressive illocutionary acts, 4 declarative illocutionary acts and 1 commissive illocutionary act , (3) The dominant speech act theory is illocutionary speech act. Illocutionary speech acts are actions carried out with the aim of conveying a specific purpose which will later affect the speech partner.